'How Can We Alter the Crest and the Spur of the Fighting Cock?': Julian Huxley, Popular Biology, and the Feminist Pacifism of Virginia Woolf. Issue 3 (2nd July 2020) - Livingstone, Catriona
Abstract: This paper takes as its starting point a letter written by Virginia Woolf in 1940 which speculates about the possibility of ending war. 'Can we change sex characteristics?' Woolf asks. 'How can we alter the crest and the spur of the fighting cock?' In writing this letter, Woolf recalls a passage she read in 1932 from the biological textbook The Science of Life, co-written by Julian Huxley: a passage which, in Woolf's terms, describes a 'hen that became a cock or vice versa'. The paper demonstrates that Woolf's writing of this period, particularly Three Guineas and Between the Acts, responds to Huxley's works of popular biology, specifically their discussion of secondary sex characteristics, hormones, and the mutability of biological sex, in order to envision a way out of the repeating cycle of violent domination that she traces in contemporary society, and to conceive of a future society not built upon a binary model of sex or gender. It proposes a non-linear conception of feminist history in which Woolf's texts—with their depiction of sex as plural and alterable through human agency—display a sympathy with our current understanding of sex: an aspect of her writing that has been overlooked by intermediate commentators.